Structure of ground-foraging ant assemblages in relation to land-use change in the northwestern Mediterranean region (Biodiversity and Conservation, 2003)
The abandonment by humans of marginal and less productive zones signiﬁes an important change in land use in North Mediterranean agroecosystems. Human perturbations have led to a highly diversiﬁed landscape, with a mosaic made up of patches of land at different stages of succession, from cultivated ﬁelds to closed forest. Our aim here is to characterize ant assemblages and their functional groups in response to these land-use changes. This progressive abandonment results in an initial increase in ant richness and abundance, which can reach high levels if the succession proceeds as far as woodland. In terms of the ant functional groups, this land-use change implies: (1) the appearance of Subordinate Camponotini; (2) an increase in Generalized Myrmicinae, Cryptics and Cold-climate specialists in terms of ant species richness, overall abundance and, for Generalized Myrmicinae and Cryptics, an increase in abundance percentage; (3) a decrease in percentage abundance of Opportunists; (4) a progressive decrease in species richness as well as overall and percentage abundance of Hot-climate Specialists throughout the transformation from crops to woodlands; and (5) an initial increase of Dominant Dolichoderinae followed by a decrease in ant species richness, overall abundance and percentage abundance. Using the ant functional group approach for the clearly separate stages of the regeneration process is a promising method for comparing responses of ant communities to human land use.